1984
DOI: 10.1002/chin.198434325
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: THE SYNTHESIS AND METAL BINDING CHARACTERISTICS OF NOVEL, ISOPOLAR PHOSPHONATE ANALOGS OF NUCLEOTIDES

Abstract: Kondensation entsprechender Bis‐phosphonsäuren (II) [als Bis‐(tributylammonium)‐Salze] mit Adenosin‐ bzw. Guanosin‐5′‐phosphorsäure‐ morpholiden (I) (als Morpholin‐4‐N,N′‐dicyclohexylcarboxamidiniumsalze) liefert Nucleotid‐Analoge (III) von ATP bzw. GTP (isoliert als Tetra‐Li‐Salze in den angegebenen Ausb.), von denen (IIIa)‐(IIIc) mit diesen isopolar und isoster sind.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 1 publication
2
6
0
Order By: Relevance
“…52,59 The smaller size of the β , γ -methylene group presumably allows tighter receptor binding than the larger β , γ -dihalomethylene group, consistent with the EC 50 values at the P2Y 1 R obtained for analogues 13 and 14 (Table 2). …”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…52,59 The smaller size of the β , γ -methylene group presumably allows tighter receptor binding than the larger β , γ -dihalomethylene group, consistent with the EC 50 values at the P2Y 1 R obtained for analogues 13 and 14 (Table 2). …”
Section: Discussionsupporting
confidence: 80%
“…Earlier, we reported that 2-MeS-β,γ-methylene-ATP was a potent and selective P2Y 1 receptor (P2Y 1 R) agonist. 27 Here, we examined whether a β,γ-dihalomethylene substitution in analogues 8-14 would enhance agonist potency at the P2Y 1 R due to the reduced pK a of the terminal phosphonate (∼7), as compared to the pK a of 8.4 52 for the corresponding methylene derivatives. Because analogues 8-14 should be 90% ionized under physiological conditions (vs 9% ionization for analogue 1), we expected that negatively charged phosphonates in analogues 8-14 would increase binding to the P2Y 1 R. Accordingly, the activities of analogues 8-14 were determined at the turkey P2Y 1 R heterologously expressed in human 1321N1 astrocytoma cells that are devoid of endogenous P2Y receptors.…”
Section: Resultsmentioning
confidence: 99%
“…The ss-siRNA 63 containing 5′- trans -fluorovinylphosphonate (( E )-5′-F-VP) modification showed higher potency (IC 50 7 nM; Figure 13 ) relative to 5′- cis -vinylphosphonate (( Z )-5′-VP) 64 (IC 50 40 nM; Figure 13 ). It is surprising that ss-siRNA 63 was 7-fold less potent than ss-siRNA 61 given that fluorination of the alpha carbon of the 5′-VP modification ( 38 , 39 ) was expected to be isoelectronic compared to the phosphate. These data demonstrate that the factors other than electronics are contributing to the activity of ( E )-5′-VP ss-siRNA.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, published 13 P NMR data for diphosphate analogues bearing a β,γ-methylene bridge substituted with bulky and anionic functions did not shown an increase of the 2 Jβγ coupling constant. 34 This unusual degree of electronic interaction between β and γ the phosphorus atoms, previously reported in other series for difluoromethylene diphosphate analogues, 35 37 reflects a complex set factors including the combined electronegativity and dπ-bonding possibilities for a β-P ligand which may led to conformational changes in the phosphoryl chain. 35 …”
Section: Discussionmentioning
confidence: 59%